PENGENDALIAN GULMA UMUM DENGAN HERBISIDA CAMPURAN (Amonium Glufosinat 150 g/l dan Metil Metsulfuron 5 g/l) PADA TANAMAN KELAPA SAWIT TBM - Uum Umiyati; Denny Kurniadie (Jurnal Penelitian Kelapa Sawit, 2018)
This experiment was carried out with the objecti ve of knowing the effectiveness of mixed herbicides with the active ingredients Ammonium Glufosinat 150 g/l and Methyl Metsulfuron 5 g/l for controlling common weeds in unproduced palm crops. The experiment was conducted at Sagala Herang Plantation in Serang Panjang Sub-district, West Java. The experimental design used was a randomized block design with four replicates and six treatments then tested further with Duncan test at 95% confidence level. The mixed herbicide treatments tested were -1 Ammonium Glufosinate 150 g/lg L and Methyl - 1 - 1 Metsulfuron 5 g L dose 193. 75 l Ha, mixed ammonium Ammonium Glufosinate 150 g L and -1 - 1 - 1 Methyl Metsulfuron 5 g L doses 387. 5 l Ha, Ammonium Glufosinat 150 g/l mixed herbicide and -1 -1 Methyl Metsulfuron 5 g L dose 581.25 l Ha , and herbicide mixture of active ingredient Ammonium -1 -1 Glufosinat 150 g L and Methyl Metsulfuron 5 g L dose -1 775 l Ha , manual weeding and without treatment (control). The results showed that Herbicide herbicide mixture of active ingredient Ammonium Glufosinat 150 -1 -1 g L and Methyl Metsulfuron 5 g L with dose 193.75 -1 775 l Ha is an effective herbicide controlling weed grass such as Ottochloa nodosa L, Imperata cylindrica L, and wide leaf weeds Ageratum conyzoides L and total weeds on oil palm cultivation aged 2 - 4 years until age of observation 12 MSA and did not cause poisoning in palm oil plant TBM until observation three weeks afterapplication.